) Solve the ODE y+4y+4y= e−2x using the method of variation of parameters x3
Given that:-
"y''+4y'+4y=e^{-2x}"
In operator form
"(D''+4D+4)y=e^{-2x}"
Where "f(D)=(D^{2}+4D+4)"
"R=e^{-2x}"
The A.E is
"f(m)=0 \\implies m^2+4m+4=0 \\implies (m+2)^2=0\\\\\n\\implies m = -2, -2\\\\\n\\therefore y_c=C_1e^{-2x}+C_2xe^{-2x}\\\\\ny_p=AU+BV\\\\\nU=e^{-2x}\\ ;\\ U'=-2e^{-2x}\\ ;\\ \\\\\nV=xe^{-2x}\\ ;\\ V'=-2xe^{-2x}+e^{-2x}\\ \\\\\nUV'+VU'=-2xe^{-4x}+e^{-4x}+2xe^{-4x}=e^{-4x}\\\\\n\\\\\n\\therefore A=\\intop \\frac{-VR}{UV'-VU'}dx= - \\intop \\frac{xe^{-4x}}{e^{-4x}}dx = -\\intop xdx\\\\\n= -\\intop xdx + \\intop [\\intop xdx]dx\\\\\n= -\\frac{x^2}{2}+\\intop \\frac{x^2}{2}dx = -\\frac{x^2}{2} + \\frac12 \\intop x^2dx\\\\\n\\implies -\\frac{x^2}{2} + \\frac12 \\cdot \\frac{x^3}{3} = -\\frac{x^2}{2} + \\frac {x^3}{6}\\\\\n\n\\therefore B=\\intop \\frac{-UR}{UV'-VU'}dx= \\intop \\frac{e^{-2x} \\cdot e^{-2x}}{e^{-4x}}dx= \\intop dx\\\\\n= \\intop dx-\\intop [\\intop dx]dx\\\\\n=x-\\intop xdx = x-\\frac{x^2}{2}\\\\\n\\implies y=y_c+y_{p}=C_1e^{-2x}+C_2xe^{-2x}+(x-\\frac{x^2}{2})e^{-2x}+ (\\frac{x^3}{6} +\\frac{x^2}{2})e^{-2x}"
Comments
Leave a comment